Fe-Containing Al-Based Alloys: Relationship between Microstructural Evolution and Hardness in an Al-Ni-Fe Alloy - Faria, Jonas; de Paula, Andrei; Silva, Cássio; Kakitani, Rafael; Barros, André; Garcia, Amauri; Brito, Crystopher [UNESP]; Cheung, Noé (MDPI, 2023)
Recycled Al alloys not only offer environmental and economic benefits but also present a valuable base for the development of innovative materials, such as Al-Ni-Fe alloys. This work particularly focuses on the microstructural changes and hardness of an Al-5Ni-1Fe alloy (wt.%) solidified with an approximate 20-fold variation in cooling rates. For the various microstructural length scales obtained, only the eutectic regions exhibit a uniform pattern, with the eutectic colonies comprising an α-Al phase along with Al3Ni and Al9FeNi intermetallic compounds. It is shown that microstructural refinement can lead to a 36% increase in hardness. To represent this mathematically, hardness values are associated with the eutectic colony and intermetallic fiber spacings (λEC and λIF is, respectively) using experimental equations based on the Hall–Petch relationship and multiple linear regression. In addition, comparisons are undertaken with Al-5Ni and Al-1Fe (wt.%) alloy samples produced under the same conditions. The Al-5Ni-1Fe alloy exhibits higher hardness values than both the Al-5Ni and Al-1Fe binary alloys. Furthermore, the hardness of the ternary Al-Ni-Fe alloy is sensitive to microstructural refinement, a characteristic absent in the binary alloys. For λIF−1/2 = 1.56 µm−1/2 (coarser microstructure), the Al-5Ni-1Fe alloy exhibits a hardness of about 13% and 102% higher than that of the Al-5Ni and Al-1Fe alloys, respectively, while for λIF−1/2 = 1.81 µm−1/2 (finer microstructure), it demonstrates a hardness of approximately 39% and 147% higher as compared to that of the Al-5Ni and Al-1Fe alloys, respectively. Thus, this research provides experimental correlations that connect hardness, microstructure, and solidification thermal parameters, contributing to a better understanding for the design of as-cast Fe-contaminated Al-Ni-based alloys.
Keywords: Al alloys; hardness; microstructure; recycling; solidification